2005
DOI: 10.1002/chem.200400892
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Conformations of Peptides Containing tert‐Leucine, a Sterically Demanding, Lipophilic α‐Amino Acid with a Quaternary Side‐Chain Cβ Atom

Abstract: Terminally protected homopeptides of tert-leucine, from the dimer to the hexamer, co-oligopeptides of tert-leucine in combination with alpha-aminoisobutyric acid or glycine residues up to the hexamer level, and simple dipeptides representing known scaffolds for catalysts in asymmetric organic reactions were prepared by solution methods and fully characterized. The results of conformation analysis, performed by use of FT-IR absorption, NMR, CD, and X-ray diffraction techniques, indicate that this hydrophobic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…[51] Comparison of the new crystal structure of inhibitor 19 with the previously solved furin structures in complex with P3 Vala nalogues [21] revealed that the terminal methyl groups of Valc an be perfectly superimposed with two sidechain methyl groups found in the Tle structure. For the additional third methyl group in Tle, we could not identify any specific contact with furin that could easily explain the improved affinity.I ti s, however,i nvolved in additional close intramolecular van der Waals contacts to the amide hydrogen atom (with ad istance to the nitrogen of 3.1 ) and to the carbonyl oxygen atom (3.5 ) of the P2 Arg residue.…”
Section: Discussionmentioning
confidence: 95%
“…[51] Comparison of the new crystal structure of inhibitor 19 with the previously solved furin structures in complex with P3 Vala nalogues [21] revealed that the terminal methyl groups of Valc an be perfectly superimposed with two sidechain methyl groups found in the Tle structure. For the additional third methyl group in Tle, we could not identify any specific contact with furin that could easily explain the improved affinity.I ti s, however,i nvolved in additional close intramolecular van der Waals contacts to the amide hydrogen atom (with ad istance to the nitrogen of 3.1 ) and to the carbonyl oxygen atom (3.5 ) of the P2 Arg residue.…”
Section: Discussionmentioning
confidence: 95%
“…In structure-supporting solvents, Tle homopeptides are much less folded than their Leu, Val, or Ile counterparts, and they tend to extensively self-associate. 13 Structural analyses of a combination peptide composed of α-aminoisobutyric acid (Aib) and Tle have also been performed. 13 Aib is strongly helicogenic due to its gemdimethylation at the α-carbon, 14,15 and Aib homopeptides adopt a 3 10 -helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…The amphipathic helical structure along residues 8–13 is likely responsible for the superior antimicrobial activity of the substituted peptides whereas the partial lack of helicity in DNal probably contributes to its reduced activity. Indeed, the residues Deg [26], tButGly [27], Ac3c [36], β-Ala [31], and Acpc [32], which do not stabilize regular right handed helices, did not promote activity in the corresponding peptides.Therefore, consistent with previous observations, the amphipathic helical content proved to be a key factor in the activity of antimicrobial peptides [37], [38].…”
Section: Resultsmentioning
confidence: 95%
“…Conversely, diethylglycine (Deg) containing peptides have a greater tendency to form extended backbone conformations in strongly interacting solvents such as water [26]. Similarly, the tert -butyl glycine (tButGly) also called tert -leucine residue, inserted in peptide 3 , prefers extended (β sheet-like) or semiextended [(Pro) n -like] conformations [27]. Peptides 1 and 2 containing an Aib and a Deg residue in position 10, respectively, did not show antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%